Pengaruh Kurs, Keterbukaan Perdagangan, Produktivitas, Kredit Domestik Terhadap Volume Ekspor di Negara ASEAN - Teresia Icha Oktaviana; Imam Awaluddin; Mega Mariska (CV. ITTC INDONESIA, 2026)
The ASEAN region has experienced rapid trade growth, but differences in export performance persist among member countries. These differences are related to variations in exchange rate stability, trade openness, labor productivity, and access to domestic financing. This study aims to analyze the effects of exchange rates, trade openness indices, productivity, and domestic credit on export volume in eight ASEAN countries: Indonesia, Malaysia, Thailand, Singapore, the Philippines, Vietnam, Cambodia, and Brunei Darussalam, over the period 2010–2024, using quarterly data. The method used is the Panel Autoregressive Distributed Lag (Panel ARDL) model with the Pooled Mean Group (PMG) approach to identify short-run and long-run relationships. The analysis steps include stationarity tests, cointegration tests, and long-run coefficient estimation and adjustment mechanisms. The results indicate a long-run relationship between the variables. Overall, the trade openness index, productivity, and domestic credit have a positive effect on export volume, while the exchange rate has a negative effect in the long run. In the short run, trade openness has a positive effect, while the exchange rate, productivity, and domestic credit have a negative effect. These results confirm that increased production competitiveness and domestic financial support are crucial factors in strengthening regional export performance. These findings are expected to serve as considerations for relevant parties for further development and learning. The ASEAN region has experienced rapid trade growth, but differences in export performance persist among member countries. These differences are related to variations in exchange rate stability, trade openness, labor productivity, and access to domestic financing. This study aims to analyze the effects of exchange rates, trade openness indices, productivity, and domestic credit on export volume in eight ASEAN countries: Indonesia, Malaysia, Thailand, Singapore, the Philippines, Vietnam, Cambodia, and Brunei Darussalam, over the period 2010–2024, using quarterly data. The method used is the Panel Autoregressive Distributed Lag (Panel ARDL) model with the Pooled Mean Group (PMG) approach to identify short-run and long-run relationships. The analysis steps include stationarity tests, cointegration tests, and long-run coefficient estimation and adjustment mechanisms. The results indicate a long-run relationship between the variables. Overall, the trade openness index, productivity, and domestic credit have a positive effect on export volume, while the exchange rate has a negative effect in the long run. In the short run, trade openness has a positive effect, while the exchange rate, productivity, and domestic credit have a negative effect. These results confirm that increased production competitiveness and domestic financial support are crucial factors in strengthening regional export performance. These findings are expected to serve as considerations for relevant parties for further development and learning.